ISLAM AND ITS OPPOSITION FACTORS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Today, Islam is flourishing, the number of Muslims among the world's population is increasing, which is causing groups that are enemies of Islam to introduce the concept of "Islamophobia" about Islam, therefore we decided to write this article using hadiths and collections from the books of famous scholars aimed at revealing the true essence of Islam.